Implementation of Standard of Graduate Competence in The Curriculum 2013 in Elementary Schools - Ndaru Mukti Oktaviani; Isnaini Wulandari (JOURNAL OF TEACHING AND LEARNING IN ELEMENTARY EDUCATION (JTLEE), 2019)
Government certainty related to curriculum development from KTSP to Curriculum 2013 raises a new challenge for teachers. Implementation Curriculum 2013 in elementary schools still faced significant problems where based on the focus group discussion results with elementary school teachers in the Kuningan area of West Java, it was known that teachers still had difficulty implementing thematic-integrative with connecting the material with other material. Purpose of this study is 1) describes the problems faced by elementary school teachers for the standard of graduate competence in the implementation of the  Curriculum 2013 in elementary schools, 2) describes the factors that cause problems standard of graduate competence in the implementation of  Curriculum 2013in elementary schools. The research method used in this study is descriptive qualitative. The research design used descriptive steps of a case study. The research subjects were teachers and students in elementary school at SDN 1 Manis Lor, Jalaksana District, SDN 1 Purwawinangun, Kuningan District and SDN Dukuhdalem, Japara District, Kuningan Regency. Data collection techniques are used using observation, interviews and documentation studies. Data analysis used refers to the analysis of qualitative research data.